A full-range analysis of anchorage failure for reinforced concrete beams in chloride environment. (November 2019) - Chen, Meng-Cheng; Yang, Chao; Fang, Wei; Xie, Li
Abstract: To examine the mechanical properties of corroded reinforced concrete (RC) beams, beam specimens and pull-out test specimens are subjected to accelerated electrochemical corrosion. Then this paper input the test parameters into a numerical model to perform a full-range nonlinear numerical analysis. It is found that bond slip relationship from pull-out test is not suitable for being used in beam test; cover spalling will affect the distribution of bond slip; with the increase in corrosion level, the bond strength of RC decreases after an initial increase; When the corrosion level exceeds micro-rust stage (0~3%), the bearing capacity of RC beams will keep declining. Highlights: An empirical bond degradation model of corrosion reinforced concrete beam is proposed. A modified bond slip constitutive relationship for the beam test has proposed in this study. The distribution of bond slip during different loading stages was discussed. This paper also predicted the test beam with deep corrosion level of steel bar.